MENINGKATKAN RASA PERSAUDARAAN DAN SOLIDARITAS PERTEMANAN ANTAR SISWA UNTUK MENGHINDARI BULLYING - Asridah Warni Tanjung; Nindie Ellesia; Intan Sari Budiharjo; Umar Hanis (Universitas Pamulang, 2020)
The purpose of Community Service Activities is to carry out one of the Higher Education Tri Dharma. In addition, it is expected that through community service, the existence of higher education institutions can make a major contribution to the development and application of knowledge to the community. The method of activity used is that we go to the 26 Bintaro State PKBM school which is located at Jl. Bintaro Permai III / 30B, Ex. Bintaro, Kec. Pesanggrahan, City Administration of South Jakarta and will provide training there on 10-12 October 2019. This training aims to make students and students who attend PKBM 26 Bintaro, especially in the PKBM program, increase fraternity and friendship solidarity between students to avoid bullying in socialize in their environment and the world of work. The results of community service obtained were increased knowledge for Participants (Students) of the 26th State PKBM Bintaro so that they had a good view of the importance of increasing the sense of brotherhood and friendship solidarity among students because of our participation as qualified generations of the nation (HR) for quality entering the world of work and how important it is to improve the quality of themselves to avoid bullying in socializing and the world of work. The knowledge gained at Community Service this time is expected to be able provide new enthusiasm for us in delivering material and motivation and contribute to the younger generation, both within the school, campus and environment family.Keywords: Brotherhood, Solidarity, Bullying